PENERAPAN KONSEP BERKELANJUTAN DENGAN TEMA BARN HOUSE DALAM DESAIN CABIN DI KAWASAN EKOWISATA KOPI KELOMPOK TANI MANGLAYANG - Wijaya, Gisela; Kusnaedi, Iyus (INSIDE : Jurnal Desain Interior, 2023)
The Manglayang farmer group coffee area has great potential as an ecotourism site. This is related to agricultural products that can penetrate the international market and are well known in various countries. Even though it has entered the international market, the facilities available are still inadequate, such as accommodation areas to support visitor accommodation. One solution to improve accommodation facilities and facilities is through design, using the design by research method to create accommodation areas in the Manglayang farmer group coffee area. Through designing a cabin with a sustainable approach that has novelty and closeness to nature, the cabin design aims to utilize the land and produce novelty with a barn house theme orientation with the use of skylights with PDLC material technology and the use of natural waste, namely coffee tree twigs. So it will produce a design that provides a new atmosphere in the middle of a coffee plantation and provides a return to nature experience for guests staying in the Manglayang Farmers Group Coffee Ecotourism Area.